KONSTRUKSI SMART LEARNING LUMI EDUCATION PADA PEMBELAJARAN SUHU DAN KALOR UNTUK KETERAMPILAN PROSES SAINS SISWA KELAS XI SMA - Afriani, Dita; Nasir, Muhammad; Rahmad, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science process skills are essential competencies in physics learning because they support students' critical thinking and problem-solving abilities. However, students often experience difficulties in understanding abstract concepts, particularly on temperature and heat topics, resulting in low science process skills. This study aimed to develop Smart Learning media based on Lumi Education and determine its validity and reliability for physics learning on temperature and heat materials. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The products developed included Smart Learning media and science process skills test instruments. Product validity was evaluated by three physics education lecturers and two physics teachers, while reliability was analyzed using Cronbach’s Alpha. The results showed that the developed Smart Learning media and science process skills test instruments achieved very high validity scores and met the reliability criteria. The Smart Learning media obtained validity indices of 0.909 and 0.996, indicating that the media is suitable for use in physics learning. Therefore, the developed Smart Learning media based on Lumi Education is considered valid and reliable and can support the development of students’ science process skills in learning temperature and heat.